Trauma Narratives of Scottish Childhood in Janice Galloway’s Short Stories - Jelínková, Ema (American & British Studies Annual, 2022)
Janice Galloway represents one of the most strikingly original voices in new Scottish fiction, which breaks with the tradition of conventional narratives looking back at the national history and looking up to larger-than-life male heroes. Instead, Galloway writes deftly crafted short stories of everyday life in contemporary settings, finding that the past informs the present and proceeding to explore how the stateless nation’s cultural heritage affects her characters. This paper analyses selected stories from Galloway’s collections Blood (1991) and Where You Find It (1996) from the perspective of trauma criticism, which seems a particularly fitting approach to the author’s often disturbing narratives of violence and abuse. The focus is on child characters and on the ways that historical trauma, as introduced by Sigmund Freud and further refined by Cathy Caruth, is passed down to them. Finally, the paper provides examples from the individual short stories which illustrate how the traumatic experience can be acknowledged, witnessed, and ultimately communicated.